Laryngeal Leishmaniasis - Moraes, Bruno Teixeira de; Amorim Filho, Francisco de Souza; Caporrino Neto, José; Saraceni Neto, Paulo; Melo Júnior, José Elson Santiago de (International Archives of Otorhinolaryngology, 2012)
Introduction: Leishmaniasis is classified into three clinical presentations: visceral, coetaneous and mucocutaneous. The latter is usually secondary to hematogenous spread after months or years of skin infection and can manifest as infiltrative lesions, ulcerated or vegetating in nose, pharynx, larynx and mouth, associated or not with ganglionics infarction. Laryngeal involvement is part of the differential diagnosis of lesions in this topography as nonspecific chronic laryngitis, granulomatosis and even tumors of the upper aerodigestive tract presenting atypical evolution. Sometimes it is difficult for the correct diagnosis of Leishmaniasis, with description of cases in the literature were conducted improperly. Objective: The objective of this study is to report a case of laryngeal Leishmaniasis addressing the difficulty of diagnosis, complications and treatment applied. Case Report: A patient with pain throat, dysphagia, odynophagia, dysphonia and weight loss, with no improvement with symptomatic medication. At telelaringoscopy, infiltrative lesion showed nodular supraglottis. He underwent a tracheotomy for airway obstruction and biopsy with immunohistochemical study for a definitive diagnosis of laryngeal Leishmaniasis. The patient was referred to the infectious diseases that initiated treatment with N-methylglucamine antimoniate with satisfactory response to therapy. Final Comments: Faced with a clinical suspicion of granulomatous diseases, it is essential to follow protocol laboratory evaluation associated with histological injury, to get a precise definition etiological without prolonging the time of diagnosis. Medical treatment for mucosal Leishmaniasis, recommended by the World Health Organization, was adequate in the case of laryngeal disorders, with complete resolution of symptoms.